Prolonged Unconsciousness Following Severe COVID-19. (9th March 2021) - Abdo, Wilson F.; Broerse, Catharina I.; Grady, Bart P.; Wertenbroek, Agnes A.A.C.M.; Vijlbrief, Onno; Buise, Marc P.; Beukema, Menno; van der Kuil, Mark; Tuladhar, Anil M.; Meijer, Frederick J.A.; van der Hoeven, Johannes G.
Abstract : Objective: We report a case series of patients with prolonged but reversible unconsciousness after coronavirus disease 2019 (COVID-19)–related severe respiratory failure. Methods: A case series of patients who were admitted to the intensive care unit due to COVID-19–related acute respiratory failure is described. Results: After cessation of sedatives, the described cases all showed a prolonged comatose state. Diagnostic neurologic workup did not show signs of devastating brain injury. The clinical pattern of awakening started with early eye opening without obeying commands and persistent flaccid weakness in all cases. Time between cessation of sedatives to the first moment of being fully responsive with obeying commands ranged from 8 to 31 days. Conclusion: Prolonged unconsciousness in patients with severe respiratory failure due to COVID-19 can be fully reversible, warranting a cautious approach for prognostication based on a prolonged state of unconsciousness.